Sexual Deviation of Animals Between Law and Sharia: a Comparative Analysis - Darwis, Sri Astuti Ana; Haddade, Abdul Wahid; Akmal, Andi Muhammad (Mazahibuna: Jurnal Perbandingan Mazhab, 2021)
Bestiality is a form of sexual perversion. Bestiality perpetrators seek sexual satisfaction by making animals objects of sexual satisfaction, which is considered to deviate from legal norms, religious norms, and moral codes that apply in society. This article aimed to discuss the comparison of Islamic law and positive law regarding the sexual perversion of animals. This study employed qualitative with a comparative descriptive research approach. The results of this study indicated differences of opinion between Islamic law and positive law regarding the sexual perversion of animals. Based on the different views of Islamic law in response to this case, some people were allowed, and some were not allowed. Meanwhile, some people stated that the incident must be subject to sanctions and fines from a positive legal perspective. The implication of this study was to prevent bestiality (sexual activity of animals), it is necessary to have strict and concrete rules to protect the next generation of the nation, as a good legal policy as well as renewal of Islamic law and positive law as well as protection of animals. Providing information is very necessary through maximum socialization to the public about the law of consuming animals that humans have fertilized.